APPLYING LIFE CYCLE ASSESSMENT TO ANALYSE RESOURCE CONSUMPTIONS AND WASTE GENERATION IN A LABORATORY ANIMALS PRODUCTION - Viana, Ingrid Daré; Peixoto, José Antonio Assunção; Xavier, Leydervan de Souza; de Souza, Cristina Gomes (Brazilian Journal of Operations & Production Management, 2016)
The objective of this study was to quantify and analyze resource consumptions of a laboratory rabbits production, in a Brazilian animal research facility, in order to produce a harmonized Health-Care Waste (HCW) classification, according to national regulations and international guidelines, as it is a basis to perform health and safety risk analysis, of animals, humans and environment impacts in HCW management. Methodologically, the principles and framework from Life Cycle Assessment were used to produce a door‑to‑door Life Cycle Inventory to produce the HCW classification and a short environmental impact assessment. A high electricity consumption (about 96%), for conditioning facilities maintenance, and a high water consumption transformed into effluents and emissions (about 97.5%) were observed. Specifically, from HCW classification a first analysis of mass pointed: effluents (45.92 %), emissions (52.54 %), biological waste (1.45%) and common waste (0.001 %). These data are primary estimates that lead to deeper analysis of toxic materials and contamination. Finally, the entire study produced a cross fertilization of information giving more transparency about the rationality implied in the modeling of processes and presentation of reports, enabling to relate the local scope of impact assessment through broader reflections on global social responsibility and eco-efficiency.